2015
DOI: 10.1007/s11423-015-9389-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy relevant to competitive anxiety and gameplay interest in the one-on-one competition setting

Abstract: Individual gameplay interest is affected by numerous factors and a competition setting is also of importance as there are factors that need to be managed. To understand the motivational variables related to an educational game competition, this study explored the interrelatedness between self-efficacy, competitive anxiety, and gameplay interest in a one-on-one Chinese idiom string up game competition. Effective data from 278 elementary school students from grades five to six were collected and subjected to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…Further effects might be induced depending on whether the competitive goal is aligned with the underlying learning goal, especially as learners might struggle to transfer from competitive to learning behavior (Chen 2014 ) or no deep learning is triggered (DeLeeuw and Mayer 2011 ). Individual or cultural differences (e.g., different prior knowledge; ter Vrugte et al 2015 ; competitive anxiety; Hong et al 2015 ; cultural norms; Gibbons and Buunk 1999 ) alter the outcomes of learning processes even further. If the learning material includes more complex social cues (e.g., virtual representations of the competitors and their actions), extraneous cognitive load could be induced as well (Nebel et al 2016b ), although this may depend on how social data is presented (Schnaubert et al 2020a ).…”
Section: Social Cues In Interactive Learning Materialsmentioning
confidence: 99%
“…Further effects might be induced depending on whether the competitive goal is aligned with the underlying learning goal, especially as learners might struggle to transfer from competitive to learning behavior (Chen 2014 ) or no deep learning is triggered (DeLeeuw and Mayer 2011 ). Individual or cultural differences (e.g., different prior knowledge; ter Vrugte et al 2015 ; competitive anxiety; Hong et al 2015 ; cultural norms; Gibbons and Buunk 1999 ) alter the outcomes of learning processes even further. If the learning material includes more complex social cues (e.g., virtual representations of the competitors and their actions), extraneous cognitive load could be induced as well (Nebel et al 2016b ), although this may depend on how social data is presented (Schnaubert et al 2020a ).…”
Section: Social Cues In Interactive Learning Materialsmentioning
confidence: 99%
“…Un factor asociado a las competencias deportivas es la ansiedad competitiva, definida como el sentimiento subjetivo de aprensión o amenaza, acompañada de un incremento de la actividad fisiológica, que aparece en contextos de gran demanda emocional y física (Rodríguez, López, Gómez, & Rodríguez, 2015). Se produce frente a "una situación potencialmente estresante" (García-Mas et al, 2015, p. 21), lo que afecta el desempeño de los atletas y disminuye notablemente su eficacia y rendimiento (Hong, Hwang, Tai, & Lin, 2015).…”
Section: Ansiedad Competitivaunclassified
“…Research has revealed that self-efficacy had a direct effect on interest [43]. Past studies have confirmed that improving students' sense of self-efficacy for specific tasks helped to increase players' interest in playing games in a competitive environment [44]. There is also a study based on game-based learning showing that self-efficacy and interest were positively correlated [45], and a study of Thai language learning had the same results, as they found that self-efficacy and interest were positively correlated [46].…”
Section: A Relationship Between Youtube Self-efficacy and Learning Interestmentioning
confidence: 99%
“…Rottinghaus et al stated that self-efficacy and interest were mutually independent but interrelated dimensions, while the study of Chiang et al showed that self-efficacy had a direct effect on interest [42]. In addition, Hong et al further found that improving students' sense of self-efficacy for specific tasks will help increase players' interest in playing games in a competitive environment [44]. Hong and Chan's study on game-based learning indicated that self-efficacy and interest were positively correlated [45].…”
Section: A Youtube Self-efficacy Was Positively Related To Learning Interestmentioning
confidence: 99%